PENGARUH PENGGUNAAN KEMASAN TERHADAP MUTU KUKIS SUKUN - Michael Johnrencius; Netti Herawati; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to determine the best type of packaging to wrap breadfruit cookies. Research used a Completely Randomized Design (CRD) with two factor treatments and three replications. Treatment was different types of packaging as a first factor consist of A1 (without packaging), A2 (using wax paper), A3 (using plastic Polyethylene (PE)), and A4 (using plastic Polypropylene (PP)). As a second factor is the length of storage of B1 (14 days), B2 (28 days), and B3 (42 days). Parameters were water content, peroxide number, analysis of total bacterial, fungal identification (at the macro and micro) and organoleptic (descriptive and hedonic). The results showed interaction of type of packaging and length of storage significantly affected (P<0,05) the acquisition of the water content, peroxide number, and analysis of total bacterial. Type of packaging significantly affected (P<0,05) against the value of water content, peroxide number, and analysis of total bacterial. Length of storage significantly affected (P<0,05) against the value of water content, peroxide number, and analysis of total bacterial. Based on organoleptic assessment descriptively, breadfruit cookies are packed with plastic Polypropylene and plastic Polyethylene able to suppress rancidity that occurs during storage. Based on the organoleptic assessment as hedonic breadfruit cookies are packed with plastic Polypropylene and plastic Polyethylene preferred by the panelists. The best treatment is using type of packaging plastic Polypropylene.Keyword: Type of packaging, length of storage, cookies breadfruit.